Temporal patterns of tramadol in hair after a single dose. (November 2020) - Johansen, Sys Stybe; Dang, Linda Tuong Vy Le; Nielsen, Marie Katrine Klose; Haage, Pernilla; Kugelberg, Fredrik Carl; Kronstrand, Robert
Graphical abstract: Highlights: Controlled study with data from 17 subjects administered a single dose of tramadol. Tramadol present in hair to at least 4 months after single ingestion. Narrow segmental analysis of hair enabled a good estimate of time of drug ingestion. Tramadol metabolite findings may depend on subject CYP2D6 phenotype. Significant wash out and sweat effects were observed. Abstract: This controlled study aimed to measure concentrations of tramadol (TRA) and its two main metabolites, N -desmethyltramadol (NDMT) and O -desmethyltramadol (ODMT), in hair following a single dose ingestion and to investigate the distribution patterns in hair by segmental analysis of hair samples taken at several sampling time points after ingestion. An oral dose (50 or 100 mg) of TRA was administered to 17 healthy volunteers. Hair samples were collected prior to drug administration and 14, 30, 60 and 120 days after ingestion. Each sample was segmented in 5 mm segments and washed. The analytes were extracted from pulverized hair by incubation in extraction media for 18 h at 37 °C. A validated UHPLC–MS/MS method was used to quantify the analytes at a LLOQ of 0.001 ng/mg. Hair segments corresponding to the time of ingestion were positive for TRA and the metabolites of each sampling time point, although neighboring segments also showed positive results. The highest concentrations for both dosage groups were observed in the proximal segment of hair collected 14 days after ingestion for all subjects: 0.061–0.95 ng TRA/mg, 0.012–0.86 ng NDMT/mg and 0.009–0.17 ng ODMT/mg (n = 16). Generally, the TRA concentration was higher than the metabolites concentrations but depended on the CYP2D6 phenotype. The metabolite to TRA ratios were stable within a subject over the sampling time points, however it varied greatly between subjects. No significant differences in hair concentrations were found between the two dosage groups at each sampling time. Several confounding factors were identified such as hair pigmentation and internal sweat. We showed that analysis of 5 mm segments improved the determination of the exposure time after a single ingestion of TRA. In addition, in the later sampling time points the analytes were spread more between segments and the total drug amount of each later sampling time point declined up to a 100% (median: 75%) due to wash out. The presented results are important additions to the sparse literature reporting single dose of psychoactive drugs in hair.